1987
DOI: 10.1007/bf00544556
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and microcirculatory effects of different doses of prostaglandin E1 in man

Abstract: A cumulative dose response to intravenous PGE1 was established in 12 healthy volunteers. Systolic time intervals, including pre-ejection period (PEP), the ventricular ejection time (VET) and the RR-interval, were continuously determined, and transcutaneous oxygen pressure (tcpO2) was recorded. RR-intervals fell in a dose dependent manner, reaching a significantly lower level at 128 ng.kg-1.min-1 of PGE1 (basal value 842 ms falling to 756 ms). PEP decreased from 89 ms to 74 ms and the ratio PEP/VET decreased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Intravenous infusion of 2 100 ng kg-' min-I causes I system I flush, increases heart rate and decreases blood pressure and peripheral resistance in healthy subjects [38-401. Conversely, transcutaneous oxygen pressure as a parameter reflecting capillary flow was increased by 125% during an intravenous infusion of PGEl (16 ng kg-I min-I), demonstrating that the effects on local perfusion can be achieved with doses of PGEl devoid of systemic haemodynamic effects [38]. Comparable results were obtained in patients with arterial occlusive disease, during intravenous infusion of PGEl (9.5 ng kg-I min-'), using venous occlusion plethysmography [41].…”
Section: Eflects On Vascular Smooth Musclesupporting
confidence: 53%
See 1 more Smart Citation
“…Intravenous infusion of 2 100 ng kg-' min-I causes I system I flush, increases heart rate and decreases blood pressure and peripheral resistance in healthy subjects [38-401. Conversely, transcutaneous oxygen pressure as a parameter reflecting capillary flow was increased by 125% during an intravenous infusion of PGEl (16 ng kg-I min-I), demonstrating that the effects on local perfusion can be achieved with doses of PGEl devoid of systemic haemodynamic effects [38]. Comparable results were obtained in patients with arterial occlusive disease, during intravenous infusion of PGEl (9.5 ng kg-I min-'), using venous occlusion plethysmography [41].…”
Section: Eflects On Vascular Smooth Musclesupporting
confidence: 53%
“…PGEl is a potent vasodilator [6,7,37,38] in man. Intravenous infusion of 2 100 ng kg-' min-I causes I system I flush, increases heart rate and decreases blood pressure and peripheral resistance in healthy subjects [38-401. Conversely, transcutaneous oxygen pressure as a parameter reflecting capillary flow was increased by 125% during an intravenous infusion of PGEl (16 ng kg-I min-I), demonstrating that the effects on local perfusion can be achieved with doses of PGEl devoid of systemic haemodynamic effects [38].…”
Section: Eflects On Vascular Smooth Musclementioning
confidence: 99%
“…The rationale for using PGE 1 included its properties as a potent vasodilator and its reported benefit in preventing renal ischemia under hypoperfusion and ischemia [14,15]. The rate of 0.015 lg/kg/min of PGE 1 for a kidney was arbitrarily determined based on data showing that low systemic infusion rates of PGE 1 below 0.032 lg/kg/min do not cause a change in blood pressure or heart rate in healthy humans [16,17]. The renal-selective infusion of PGE 1 with RSP exerted vasodilating effects on the renal vascular system without having a significant effect on the systemic vascular system, which enabled an increase in the RSP flow and resulted in increased oxygen delivery, which should be favorable for treatment of ACRS.…”
Section: Discussionmentioning
confidence: 99%
“…The principal reactivity and susceptibility to interventions of the cutaneous perfusion might help predict the success of therapy [11]. A number of investigators have reported that tcPO 2 measured at the ischemic extremity rises when PGE 1 is infused intravenously [5,9,18]. In our pilot study we tried to find a parameter that might predict the effectiveness of a conservative approach to a patient with critical limb ischemia.…”
Section: Discussionmentioning
confidence: 99%